QUALIFYING BUSINESS COMPETITION-BASED NORMATIVE INTERPRETATION OF ARTICLE 33 CONSTITUTION 1945 REPUBLIC OF INDONESIA ABOUT THE WELFARE STATE - Matompo, Osgar Sahim (Journal of Humanity, 2017)
The Constitution of Indonesia who set about social welfare is correlated with the normative legal basis of competition efforts. The provisions of article 33 Constitution of 1945 when associated with the concept of the welfare State showed a strength of intact over the normative basis in order to realize the welfare State Indonesia. The existence of a correlation normatifisasi with competition as a consequence of the existence of legal interpretation that developed in line with market developments. Article 33 of the Constitution of 1945 of the substantive charge republic of Indonesia who correlated with the charge that competition business competition law thereby encouraging further accomplishing the welfare state. the ideas and ideals of unification between concepts of competition business with welfare had already been thought of by the founders of the country of Indonesia. It also shows that the nation has made the concept of the welfare State as a powerful legal basis in the Constitution of Indonesia which should be realized by correlated with business competition law competition law the ratification of the business in Indonesia.